Technical Feseability Study and Economic Development of Limestone at Pelawi Hill by PT. Semen Baturaja (Tbk.) in Ogan Komering Ulu Distric of South Sumatra - Subagio Badirun; Didik Susetyo; Restu Juniah (Research Centre of Inorganic Materials and Complexs, 2018)
Limestone mining for cement is increasing in Indonesia, and has been specifically included in the strategic plan of PT. Semen Baturaja (Persero) Tbk. By expanding the limestone mining in Bukit Pelawi, OganKomering Ulu Regency. From the mine, the Company targets 2,000,000 tons of limestone per year to support the plan to increase cement production to 3.4 million tons per year from 1.5 million tons per year. This study makes a technical and economic assessment of the Company's action plan. Based on detailed exploration drilling conducted, it has identified limestone sources of 80.3 million tons and 43.4 million tons of mining reserves. The quality of limestone composite in the mine by Company’s is CaO> 43% and RCO3> 78%. The value of Cut of Grade (COG) which is still categorized by ore is CaO at 30% and RCO3 is 70%. The results of this study indicate the assumption of the selling value of limestone with composite quality of Rp. 48,500 per ton with a maximum production rate of 2 million tons per year, still provides eligibility criteria for all investment parameters calculated showing IRR 13.72%, NPV (+) Rp 5,111,313,765.-, PBP for 6.42 years. The effect of increasing or decreasing cement price assumption and operational cost ± 1.5%, will give a significant effect on the rate of return on the calculation of this study.